Karl Jaspers : From Selfhood to Being. - Miron, Ronny. (Value Inquiry Book Series, 2012)
This book traces the work of German philosopher Karl Jaspers (1883-1969) from his origins as a young psychiatrist up to his maturity as an existentialist philosopher. The critique of Jaspers's thought follows his attempts to grant meaning to the human search for self-understanding. It reveals the difficulties and frustrations entailed in this search. The book reveals to the reader Jaspers's handling of these difficulties through constituting a philosophical relation toward the Being existing beyond the individual: other people, the world, and transcendence. In this book, the author conducts an ongoing dialog with existing research into Jaspers's work, and proposes her own new reading. As well as critiquing the existing interpretations, the author uncovers the challenges Jaspers's character has presented the readers. Unlike most scholars, who generally ignored Jaspers's early writings, dealing with psychiatry and psychology, this book suggests a philosophical reading of these writings. This exposes the unity of the world from which Jaspers created, first as a psychiatrist and later as a philosopher. This reading shows Jaspers's work as an ambitious attempt to formulate an original perception of the two basic themes that have interested philosophy and human thought throughout the ages: Selfhood and Being.